Daphnia magna Gut‐Specific Transcriptomic Responses to Feeding Inhibiting Chemicals and Food Limitation. (22nd July 2021) - Campos, Bruno; Piña, Benjamín; Barata, Carlos
Abstract: Transcriptomic responses combined with apical adverse ecologically relevant outcomes have proven to be useful to unravel and anchor molecular mechanisms of action to adverse outcomes. This is the case for feeding inhibition responses in the model ecotoxicological species Daphnia magna . The aim of the present study was to assess the transcriptomic responses in guts dissected from D. magna individuals exposed to concentrations of selected compounds that inhibit feeding and compare them with the responses associated to 2 levels of food restriction (low food and starvation). Chemical treatments included cadmium, copper, fluoranthene, λ‐cyhalothrin, and the cyanotoxin anatoxin‐a. Although the initial hypothesis was that exposure to chemical feeding inhibitors should elicit similar molecular responses as food limitation, the corresponding gut transcriptomic responses differed significantly. In moderate food limitation conditions, D. magna individuals increased protein and carbohydrate catabolism, likely to be used as energetic sources, whereas under severe starving conditions most metabolism‐related pathways appeared down‐regulated. Treatment with chemical feeding inhibitors promoted cell turnover–related signaling pathways in the gut, probably to renew tissue damage caused by the reported oxidative stress effects of these compounds, and inhibited the transcription of gut digestive gene enzymes and energetic metabolic pathways. We conclude that chemical feeding inhibitors, rather than mimicking the physiological response to low‐ or no‐food conditions, cause specific toxic effects, preventing Daphnia both from feeding and from adjusting its metabolism to the resulting low energy intake. Environ Toxicol Chem 2021;40:2510–2520. © 2021 SETAC